Ecology, Impacts, and Management of Common Late-season Defoliators of Southern Hardwoods. Issue 1 (2nd February 2023) - Oten, Kelly L F; Jetton, Robert M; Coyle, David R
Abstract: Late-season lepidopteran defoliators in the genera Anisota, Dryocampa, Datana, and Lochmaeus are usually considered minor pests which primarily cause aesthetic damage on hardwood trees in managed and natural areas. While foliage loss late in the season does not typically impact tree health, severe defoliation can occur on individual branches or entire trees, causing great concern to homeowners and land managers. We review the distribution, biology, damage, and management of several native late-season hardwood defoliators in the southeastern United States, including oakworms, mapleworms, yellownecked caterpillars, and variable oakleaf caterpillars. Affected hardwood trees typically leaf out the following spring even after severe defoliation. While management is seldom recommended due to timing or amount of damage, it may be warranted in certain situations. We provide management recommendations for these late-season defoliators, including chemical and nonchemical options for homeowners and land managers.